Wellness integrated mathematics - Swigris, Jody Lynn, author; Cunningham-Sabo, Leslie, advisor; Melby, Christopher L., committee member; Lucero, Rodrick S., committee member (Colorado State University. Libraries, 2011)
Wellness Integrated Mathematics (WIM) was a four-week, 8th grade mathematics curriculum that taught proportional reasoning using nutrition and fitness examples. The three objectives were to increase student knowledge of nutrition, fitness and math. WIM used a quasi-experimental, non-randomized, control/comparison design. Participants were four eighth-grade math classes in a single middle school. Two classes, totaling 47 students, were assigned to the comparison group. Two classes, totaling 48 students, were assigned to the intervention group. WIM was modeled after the successful middle school nutrition intervention, EatFit. The four-week curriculum consisted of nine lessons including a food demonstration and food tastings. To measure change in nutritional and fitness knowledge, the previously tested 21-item Wellness Integrated Mathematics Questionnaire (WIM-Q) was given to both groups before and after the intervention. Mathematical knowledge was measured by giving the Ratios and Proportions Math Exam to both groups before and after the intervention. Paired samples t-tests were performed on data from pre- and post-tests for both groups. The intervention group showed significant increases in overall (pre-test/post-test) percentage scores for: nutritional knowledge (60%/76%), p = .000; fitness knowledge (65%/80%), p = .000; and math knowledge (39%/92%), p = .000. The comparison group made only significant increases in math knowledge (22%/90%), p = .000. Results of the Wellness Integrated Mathematics Intervention indicate that a standards-based mathematics curriculum integrating nutrition and fitness can be an effective way to teach proportional reasoning while increasing nutrition and fitness knowledge.
Keywords: education; physical education; nutrition; mathematics; fitness